2022
DOI: 10.35848/1882-0786/ac9c83
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional diffusion of Mg into GaN from GaN/Mg mixture

Abstract: We evaluated Mg diffusion into GaN from GaN/Mg mixture. The diffusion depth of Mg increased with diffusion temperature from 1100 °C to 1300 °C, whereas the Mg concentration remained constant at 2–3×10^18 cm^-3 independent of temperature. The estimated activation energy for Mg diffusion was 2.8 eV, from which the substitutional diffusion mechanism was predicted. Mg-diffused GaN samples showed p-type conductivity with a maximum hole mobility of 27.7 cm^2V^-1s^-1, suggesting that substitutional diffusion contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…This speculation is based on a previous study suggested that applying hydrostatic pressure enhances Frenkel‐pair‐like annihilations of point defects in gamma‐irradiated Si and GaAs. [ 5 ] Moreover, since the Mg Ga concentration in Figure 1b (1 to 3 × 10 18 cm −3 ) agrees with the maximum concentrations of Mg in GaN doped by thermal diffusion, [ 12,35,36 ] the difference between the Mg Ga concentration at 2.0 GPa and that at 0.3 GPa indicates that the maximum concentration or solubility could be changed by the hydrostatic pressure.…”
Section: Resultsmentioning
confidence: 68%
“…This speculation is based on a previous study suggested that applying hydrostatic pressure enhances Frenkel‐pair‐like annihilations of point defects in gamma‐irradiated Si and GaAs. [ 5 ] Moreover, since the Mg Ga concentration in Figure 1b (1 to 3 × 10 18 cm −3 ) agrees with the maximum concentrations of Mg in GaN doped by thermal diffusion, [ 12,35,36 ] the difference between the Mg Ga concentration at 2.0 GPa and that at 0.3 GPa indicates that the maximum concentration or solubility could be changed by the hydrostatic pressure.…”
Section: Resultsmentioning
confidence: 68%
“…However, annealing at temperatures higher than 1,000 °C requires a masking layer to prevent incongruent decomposition of GaN. Furthermore, annealing at temperatures of more than 1,000 °C favours substitutional diffusion of Mg 55 , which could lead to thermal instability of the superlattice structure and decomposition of the interstitial Mg sheets. Temperatures lower than 550 °C might be possible but could require much longer annealing times 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown that Mg diffusion into GaN follows an exponentially decaying concentration profile; effective doping is highest at the surface. 33,37,38) For the case of 800 °C annealing, a peak surface Mg concentration of ∼3 × 10 21 cm −3 was observed with secondary ion mass spectrometry (SIMS). 33) However, only a fraction of the Mg concentration was observed to act as a substitutional dopant.…”
mentioning
confidence: 99%
“…In recent years, we have shown that the Mg diffusion process is a low-cost technology for acceptor-type doping of GaN. 37) The Mg diffusion process has been further utilized to realize low-resistance ohmic contacts to p-GaN 33) and highly efficient p-GaN SBDs. 38) At present, understanding the Mg diffusion process in GaN is still at the embryonic stage.…”
mentioning
confidence: 99%